Tribological and corrosion properties of Al–12Si produced by selective laser melting. Issue 17 (8th July 2014) - Prashanth, K.G.; Debalina, B.; Wang, Z.; Gostin, P.F.; Gebert, A.; Calin, M.; Kühn, U.; Kamaraj, M.; Scudino, S.; Eckert, J.
Abstract